A Search for Progressive Street Trading Management Model: Understanding the Principles of the Park Station Street Trading Management Model - Lande, Kwanda (My University, 2014)
Both national and local governments in parts of the global South have started to realise the importance of the informal economy in poverty alleviation. In these countries there is a growing government desire to develop informal trading policy frameworks and strategies that will not hinder the potential of the informal economy for economic growth. This is, however, often let down by varying implementation challenges. This research has focused on one specific pilot model for managing street trading around Park Station Inner city Johannesburg, a model in the making in its principles and implementation process, to investigate the extent through which its principles can be said to be progressive. This pilot model, Park Station Street Trading Management Model (PSSTMM), is set up by an alliance between a business coalition, the Central Johannesburg Partnership (CJP), and a street trading organisation, South African National Traders Retail Alliance (SANTRA). This research has documented principles and a principle renegotiation process of the PSSTMM through interviews, action research and observation that involved different stakeholders of the PSSTMM. Furthermore, as part of action research investigation of what is currently happening in the area of study in relation to street trading which were done for this research were used in the principle renegotiation process. Through this investigation the PSSTMM has shifted from only accommodating SANTRA members, a principle that existed prior to the principle renegotiation process, to accommodating all existing traders, if it happens that a design plan allow this to happen. The PSSTMM also provide support in a form cleaning and security. This is good for traders as it means more potential customers will visit the area because of improved safety and cleanliness. The PSSTMM is progressive in allowing traders, amongst other stakeholders, to be part of the policy formulation process. In this process, involved stakeholders through compromises have developed a plan agreed to by all. These principles are recognised in this research as progressive because they respond to the concepts of “inclusive” and “developmental”, which in this research are acknowledged as determining a progressive management model. However, the fee asked from street traders undermines this and I have argued that the PSSTMM to be progressive in this principle, participants of the PSSTMM need to focus on improving this principle by looking at other innovative ways. This could be done through street trader’s participation, in cleaning amongst others, to compliment the efforts of the City or of the private sector and consequently reducing the expected fee.
Planning Honours Research Reporrt 2014, Wits University
Keywords: street trading, management, policy